Evaluating High School Students' Views on Online Learning with Meeting Apps during COVID-19 - Mohammad, Wily; Maulidiyah, Nabilla Ryca (Indonesian Journal Publisher, 2023)
This descriptive qualitative research aims to explore students' experiences in online learning via meeting applications. The purposive sampling method was used to select 11 members of the